Discussion paper on economic competitiveness in the Caribbean for June 23, 1994 Roundtable in Barbados ([s.n.] [S.l.], 1994)
Discusses the main themes underlying the Caribbean Regional Development Policy Framework (CDRPF). Focuses on the relationship between the main themes and the CDRPF. Presents what CIDA hopes to accomplish at the Barbados Roundtable.
DC